Draft Genome Sequence of Amikacin- and Kanamycin-Resistant Mycobacterium tuberculosis MT433 without rrs and eis Mutations - Angkanang Sowajassatakul; Olabisi O. Coker; Therdsak Prammananan; Angkana Chaiprasert; Saranya Phunpruch (My University, 2015)
We announce the draft genome sequence of amikacin- and kanamycin-resistant Mycobacterium tuberculosis MT433, which has been previously described as the strain carrying an unknown resistance mechanism.
Keywords: Amikacin; Kanamycin; Sequence (biology); Strain (injury); Insertion sequence; Mycobacterium research and diagnosis